[Airport taxis ; PBA rookies ; Raiding the DFA [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Focuses on airport taxis that charge a special rate for ferrying incoming passengers at the Manila International Airport; new recruits to the Professional Basketball teams in the Philippines; follow-up story on the consular section of the DFA where there have been accusations of passports for sale.
Airport taxis (18 min.) -- PBA rookies (15 min.) -- Raiding the DFA (16 min.)
VHS.
Keywords: Philippines. -- Department of Foreign Affairs -- Officials and employees; Transportation, Automotive -- Philippines -- Paranaque; Basketball players -- Philippines; Passports -- Philippines